2020
DOI: 10.3389/fmed.2020.565010
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Induces Innate Immune Response and Neutrophil Activation in the Lung

Abstract: Complication in acute kidney injury (AKI) is significantly associated with developing acute respiratory failure (ARF), while ARF is one of the most important risks for AKI. These data suggest AKI and ARF may synergistically worsen the outcomes of critically ill patients and these organ injuries may not occur independently. Organ crosstalk between the kidney and the lung has been investigated by using animal models so far. This review will focus on innate immune response and neutrophil activation among the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Increased levels of plasma HNL, not differentiated between monomeric and dimeric forms, have been demonstrated to be associated with AKI severity, CRRT, and mortality in earlier studies [18,41]. The relationship observed in this study between HNL and severe AKI, with an assay aimed at neutrophil-specific dimeric HNL, suggests that neutrophils play a part in the phenomenon of lung-kidney crosstalk in critical care, where the failing of one of the two is often associated with the failing of the other, as has been proposed previously [42,43]. Earlier studies have investigated the use of whole blood and plasma NGAL as biomarkers of AKI development in intensive care, often without discriminating between the different isoforms of the biomarker [44,45].…”
Section: Discussionsupporting
confidence: 81%
“…Increased levels of plasma HNL, not differentiated between monomeric and dimeric forms, have been demonstrated to be associated with AKI severity, CRRT, and mortality in earlier studies [18,41]. The relationship observed in this study between HNL and severe AKI, with an assay aimed at neutrophil-specific dimeric HNL, suggests that neutrophils play a part in the phenomenon of lung-kidney crosstalk in critical care, where the failing of one of the two is often associated with the failing of the other, as has been proposed previously [42,43]. Earlier studies have investigated the use of whole blood and plasma NGAL as biomarkers of AKI development in intensive care, often without discriminating between the different isoforms of the biomarker [44,45].…”
Section: Discussionsupporting
confidence: 81%
“…Besides, CRRT can maintain fluid balance and homeostasis, redressing the symptoms of shock. CRRT is critical for improving the prognosis of critically ill patients [ 20 22 ]. We found that the timing of CRRT was equally important, and early CRRT could dramatically reduce the death risk for patients.…”
Section: Discussionmentioning
confidence: 99%
“…The I/R model includes unilateral and bilateral renal IR [ 92 , 93 , 94 ]. I/R leads to decline of renal function, accompanied by tubular cell necrosis and apoptosis, inflammation and oxidative stress followed by increases in blood urea nitrogen (BUN) and SCr [ 91 , 92 , 95 , 96 , 97 ].…”
Section: Renoprotective Effects Of Luteolinmentioning
confidence: 99%